Stomach content analysis reveals insights into the feeding ecology of coastal cetaceans in Sarawak, Malaysia - Ernadia Elsie Jaya, Lawrence; Cindy, Peter; Gianna, Minton; Jongkar, Grinang; melvin terry, gumal; Anna Norliza, Zulkifli Poh; Vivian, Soon; Amanda, Wilson; James, Bali; Samantha, Ambie; Dayang Nuriza, Abang Abdillah; Ian Levi, Jackery; et al. (Elsevier Science, Ltd., 2025)
This study examined the stomach contents of seven Indo-Pacific finless porpoises (Neophocaena phocaenoides), two Irrawaddy dolphins (Orcaella brevirostris), and one Indo-Pacific humpback dolphin (Sousa chinensis) retrieved from stranding and bycatch events along the Sarawak coastline. From these stomach contents, 170 fish, 150 cephalopod, and six crustacean loose prey items were found, representing 23 prey species from 18 families. Prey item importance was assessed using the percentage by number and percentage by frequency of occurrence methods as well as a modified index of relative importance. The diet of finless porpoises comprised 64% cephalopods, 33% fish and 3% crustaceans. The prey items found in Irrawaddy dolphins stomachs comprised 99% fish and 1% cephalopods. All three cetacean species were found to feed on fish across a wide range of trophic levels. Finless porpoises and Irrawaddy dolphins shared the most numerically important fish family, the Engraulidae (anchovies). Meanwhile, the Ariidae (catfish) family was the most numerically important fish family for the humpback dolphin. A few prey species found in the stomach contents (i.e. anchovies, drums or croakers, marine catfish and false trevally) are commercially important fish species in Sarawak. This overlap, coupled with previous studies that demonstrate co-occurrence of cetacean hotspots and artisanal and commercial fishing effort, suggests a high likelihood of cetacean-fisheries interactions and elevated risk of cetacean entanglement and mortality. This is a serious concern, as humpback dolphins and finless porpoises are considered Vulnerable and Irrawaddy dolphins Endangered on the IUCN Red List of Threatened Species. All dolphins and finless porpoises are also listed as Totally Protected in Sarawak’s Wild Life Protection Ordinance (1998).